Effect of Hemin on Brain Alterations and Neuroglobin Expression in Water Immersion Restraint Stressed Rats - Merhan Ragy; Fatma Ali; Maggie M. Ramzy (Scientifica)
In the brain, the heme oxygenase (HO) system has been reported to be very active and its modulation seems to play a crucial role in the pathophysiology of neurodegenerative disorders. Hemin as HO-1 inducer has been shown to attenuate neuronal injury so the goal of this study was to assess the effect of hemin therapy on the acute stress and how it would modulate neurological outcome. Thirty male albino rats were divided into three groups: control group and stressed group with six-hour water immersion restraint stress (WIRS) and stressed group, treated with hemin, in which each rat received a single intraperitoneal injection of hemin at a dose level of 50 mg/kg body weight at 12 hours before exposure to WIRS. Stress hormones, oxidative stress markers, malondialdehyde (MDA), and total antioxidant capacity (TAC) were measured and expressions of neuroglobin and S100B mRNA in brain tissue were assayed. Our results revealed that hemin significantly affects brain alterations induced by acute stress and this may be through increased expression of neuroglobin and through antioxidant effect. Hemin decreased blood-brain barrier damage as it significantly decreased the expression of S100B. These results suggest that hemin may be an effective therapy for being neuroprotective against acute stress.